Differential response of phytohormone signalling network determines nonhost resistance in rice during wheat stem rust (Puccinia graminis f. sp. tritici) colonization. (7th April 2021) - Sahu, Ranabir; Prabhakaran, Narayanasamy; Kundu, Pritha; Kumar, Aundy
Abstract: Stem rust caused by Puccinia graminis f. sp. tritici is one of the most devastating diseases of wheat. Breakdown of host resistance under field conditions triggered by the evolution of new pathogenic races and pathotypes is a perennial threat for wheat cultivation. Rice, often grown in a rice–wheat cropping system, is immune to rust infection. Our microscopic studies revealed that P . graminis f. sp. tritici, although displaying nearly identical uredospore germination, stomatal entry, and epi‐ and endophytic mycelial growth in rice and wheat, failed to sporulate to cause rust disease in rice. We identified 18 key defence signalling genes in rice and unravelled their elicitation dynamics in time‐course studies during infection. ICS1, NPR1 ‐ 3, PRs, EDS1, PAD4, FMO1 (salicylic acid [SA] signalling), and ethylene‐related genes ( ACO4 and ACS6 ) were strongly elicited in rice. However, genes from the jasmonic acid (JA) signalling pathway ( LOX2, AOS2, MYC2, PDF2 . 2, JAZ8, JAZ10 ) showed a delayed response during colonization in rice compared to an early or no induction in wheat. However, the JA/ethylene marker gene PDF2 . 2 was strongly induced in wheat as early as 12 hr postinoculation. Furthermore, rice and wheat displayed specific profiles of accumulation of various phenolic acids during P . graminis f. sp. tritici 40A infection. We propose a model where a differential modulation of the SA/JA‐dependent defence network may modulate nonhost resistance. A deeper understanding of the molecular mechanism governing differential elicitation of defence signalling may provide a novel resistance mechanism for the sustainable management of rust diseases. Abstract : Puccinia graminis f. sp. tritici colonization in rice differentially modulates phytohormone SA/JA dependent‐defence network followed by the activation of the phenylpropanoid pathway with a concomitant nonhost resistance.